2016
DOI: 10.1111/pde.12820
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Tumor Necrosis Factor α–Related Psoriatic Lesions in Children with Inflammatory Bowel Disease: Case Report and Systematic Literature Review

Abstract: We report a child with Crohn's disease and infliximab-induced guttate psoriasis. We also performed a systematic literature review on this intriguing paradoxical phenomenon in children with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Most literature to date focuses on the development of PsO secondary to treatment with antitumor necrosis factor α agents. 18 -20 We demonstrated that the risk of IBD was higher in children with PsA than in patients with PsO and no arthritis. This finding is concordant with recent work from the Netherlands that demonstrated that risk of IBD was higher in adults with PsA than in adults with PsO and no arthritis.…”
Section: Discussionmentioning
confidence: 83%
“…Most literature to date focuses on the development of PsO secondary to treatment with antitumor necrosis factor α agents. 18 -20 We demonstrated that the risk of IBD was higher in children with PsA than in patients with PsO and no arthritis. This finding is concordant with recent work from the Netherlands that demonstrated that risk of IBD was higher in adults with PsA than in adults with PsO and no arthritis.…”
Section: Discussionmentioning
confidence: 83%
“…Making this distinction is important, because drug-induced psoriasis tends to be more resistant to therapy if the offending agent is not discontinued, and drug-aggravated psoriasis may remain chronic even with discontinuation. 4,5 Unlike in our patient, the decision to discontinue the offending drug may be more difficult in other situations. This is often the case of children with inflammatory bowel disease who develop severe psoriasis secondary to the use of anti-TNF alpha agents.…”
Section: Discussionmentioning
confidence: 64%
“…A detailed review of our patient's medications pointed to drug‐induced psoriasis rather than drug‐aggravated psoriasis, which is seen more often in patients with a positive family history and genetic predisposition to psoriasis. Making this distinction is important, because drug‐induced psoriasis tends to be more resistant to therapy if the offending agent is not discontinued, and drug‐aggravated psoriasis may remain chronic even with discontinuation . Unlike in our patient, the decision to discontinue the offending drug may be more difficult in other situations.…”
Section: Discussionmentioning
confidence: 83%
“…TNF antagonists induce psoriasiform lesions in 4% to 10% of cases . Its pathogenesis remains poorly understood, but it is hypothesized that TNF inhibitors lead to increased production of interferon‐α, which leads to recruitment of Th17 cells in the skin through the chemokine receptor CXCR3.…”
mentioning
confidence: 99%
“…Genetic predisposition with genetic variants of interleukin 12 (IL‐12) and IL‐23 receptors is possible . Psoriasiform lesions are generally treated using a conventional psoriasis approach without needing to stop TNF antagonists, with a 60% to 90% success rate , although in severe cases, most doctors stop it. Ustekinumab has been described in a few adult cases as an alternative therapy for psoriasis and CD .…”
mentioning
confidence: 99%